2021
DOI: 10.1200/edbk_320691
|View full text |Cite
|
Sign up to set email alerts
|

When the World Throws You a Curve Ball: Lessons Learned in Breast Cancer Management

Abstract: In the care of patients with operable breast cancer, there has been a shift toward increasing use of neoadjuvant therapy. There are benefits to neoadjuvant therapy, such as monitoring for response, as well as an increased rate of breast conservation and reduction of potential morbidity associated with breast surgery, including axillary management. Among patients with highly proliferative tumors, such as HER2-positive or triple-negative breast cancer, those with residual disease are at higher risk of recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Again these findings were more pronounced in patients with stage I or II cancers. 18 Contrary to these findings, other studies have shown no association between delay in surgery (>30days) and overall or disease-specific survival. 18 These inconsistent findings may in part be due to different studies that lack established benchmarks that define time to surgery.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Again these findings were more pronounced in patients with stage I or II cancers. 18 Contrary to these findings, other studies have shown no association between delay in surgery (>30days) and overall or disease-specific survival. 18 These inconsistent findings may in part be due to different studies that lack established benchmarks that define time to surgery.…”
Section: Discussionmentioning
confidence: 81%
“… Retrospective cohort study 100% Johnson et al 17 Time to surgery - 12 weeks Delaying surgery for 12 weeks may decrease overall survival (OS) in BC (HR 1.46, 95% CI 1.28–1.65). OS was decreased in stages I (HR 1.27, 95%CI 1.16–1.40) and II (HR 1.13, 95%CI 1.02–1.24), but not in stage III (HR 1.20, 95% CI 0.94–1.53) Systematic review and meta analysis 100% Obeng-Gyasi et al 18 Time to Surgery - 4 weeks 6–8% increased risk of mortality for each 4-week delay in time to surgery. Delays in BC surgical care for up to 12 weeks could result in 6100 excess deaths in the US.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations